Alignment of Key Stakeholders' Priorities for Patient-Facing Tools in Digital Health: Mixed Methods Study - Courtney Rees Lyles; Julia Adler-Milstein; Crishyashi Thao; Sarah Lisker; Sarah Nouri; Urmimala Sarkar (JMIR Publications, 2021)
BackgroundThere is widespread agreement on the promise of patient-facing digital health tools to transform health care. Yet, few tools are in widespread use or have documented clinical effectiveness. ObjectiveThe aim of this study was to gain insight into the gap between the potential of patient-facing digital health tools and real-world uptake. MethodsWe interviewed and surveyed experts (in total, n=24) across key digital health stakeholder groups-venture capitalists, digital health companies, payers, and health care system providers or leaders-guided by the Consolidated Framework for Implementation Research. ResultsOur findings revealed that external policy, regulatory demands, internal organizational workflow, and integration needs often take priority over patient needs and patient preferences for digital health tools, which lowers patient acceptance rates. We discovered alignment, across all 4 stakeholder groups, in the desire to engage both patients and frontline health care providers in broader dissemination and evaluation of digital health tools. However, major areas of misalignment between stakeholder groups have stymied the progress of digital health tool uptake-venture capitalists and companies focused on external policy and regulatory demands, while payers and providers focused on internal organizational workflow and integration needs. ConclusionsMisalignment of the priorities of digital health companies and their funders with those of providers and payers requires direct attention to improve uptake of patient-facing digital health tools and platforms.